P01.041 Secondary prophylaxis with romiplostim for temozolomide-induced thrombocytopenia in newly diagnosed glioblastoma. (19th September 2018) - Le Rhun, E; Devos, P; Houillier, C; Cartalat-Carel, S; Chinot, O; Di Stefano, A; Reyns, N; Dubois, F; Weller, M
Abstract: Background: Thrombocytopenia is a major adverse event of temozolomide (TMZ) chemotherapy. It may lead to dose reduction/interruption or bleeding. Platum (NCT02227576) was a phase II open label, multicenter single arm trial evaluating the thrombopoetin receptor agonist, romiplostim, for secondary prevention of TMZ-induced thrombocytopenia in patients with newly diagnosed glioblastoma. Material and Methods: Patients diagnosed with CTCAE grade 3/4 thrombocytopenia during standard treatment of glioblastoma received weekly subcutaneous injections of romiplostim at a starting dose of 750 µg. Dose adjustments were based on weekly platelets counts. The study aimed at demonstrating that the percentage of thrombopenic patients treated with romiplostim able to complete 6 cycles of maintenance TMZ chemotherapy exceeded 10% (p0=0.10; pA=0.35) (Gerber et al., 2007). Using type I error equal to 0.05 and 95% power, 31 patients had to be recruited. According to a Fleming's two step design, an interim analysis was planned after recruitment of 20 evaluable patients. Three scenarios were pre-defined: (1) 2 patients or less meeting the endpoint: termination for futility (p<P0), (2) 6 patients or more meeting the endpoint: termination for success (p>P0), (3) 3 to 5 patients meeting the endpoint: enrollment of 11 more evaluable patients. Results: Twenty patients (13 females) were enrolled in step 1 between July 2014 and December 2016. Median age was 60.5 (range: 33–72 years). Surgery included biopsy (n=7), partial (n=5), subtotal (n=2) or gross total resection (n=6). Isocitrate dehydrogenase 1 R132H mutations were noted in 2 cases. The median lowest count of platelets at screening was 25, 500/mm 3 (range 9, 000–59, 000). Sixteen patients were enrolled after radiotherapy and before maintenance initiation, 4 were enrolled after maintenance TMZ initiation. Twelve patients enrolled in step 1 received the 6 planned maintenance TMZ cycles, corresponding to a success rate of 60% (95% confidence interval 36–81). Four of 8 patients discontinued TMZ because they did not respond to romiplostim, 2 for progression and 1 for clinical deterioration prior to completion of six cycles, 1 due to an adverse event. Eighteen severe adverse events were observed, none was judged to be related to romiplostim. The trial was terminated early for success. Conclusion: Thrombopoetin receptor agonists such as romiplostin allow to assure adequate exposure to chemotherapy in glioblastoma patients experiencing early, severe chemotherapy-induced thrombocytopenia.